Hack Tibet. - Kaiman, Jonathan (Foreign Policy)
The article mentions Dharamsala, India where Tibet's spiritual leader the Dalai Lama has lived in exile since 1959 is one of the most hacked places in the world as of November 2013 and discusses the cybersecurity efforts of the city's Tibetan community. Topics include cyberactivists' launch of a Tibetan-language messaging application called YakChat and China's efforts to block the Dalai Lama from communicating online with Tibetans.